Electrical and Photovoltaic Properties of Ag:ZnO/Si Heterojunction Device Prepared by Spray Pyrolysis Methode - Hassan, Marwa Abdul Muhsien (Al-Nahrain Journal of Science, 2012)
In this work, ZnO/p-Si and Ag:ZnO/p-Si heterostracture has been constructed on (111) oriented p-type silicon substrate using spray pyrolysis method. ZnO films were prepared with different doping ratios. The electrical and photovoltaic properties of these films have been investigated in order to get the optimum preparation conditions. The built- in potential (Vbi) is calculated under different Ag doping ratios, while from I-V measurements, the ideality factor (n) is calculated.